Position/Force Control for a Single Leg of a Quadruped Robot in an Operation Space. (20th February 2013) - Zhang, Taihui; Wei, Qing; Ma, Hongxu
For a quadruped robot, to make full use of the sensors, especially the force sensor installed on the foot and adapt to the environment well, a kind of position/force control method is proposed in this paper. A quadruped mobile robot single leg model is established in this paper and its dynamic equation in a joint space is deduced by using the Lagrange equation. Then the model is transformed in the joint space into an operation space, based on the operation space coordinates, via kinematic relations. Next the new position/force control law on the base of the operation space dynamic equation is designed. In the end, the controller in the MatLab simulation environment is tested.